Fractal parameters of soil particle size distribution in karst area, and implications of soil water repellency by plantations - Zhuo Tian; Haitao Deng; Shuaipu Zhang; Qinxue Xu; Xin Jin (Soil and Water Research)
As a critical and universal soil physical property, soil water repellency significantly affects soil and water erosion and vegetation restoration, particularly in the karst region. This study analysed soil properties, namely, particle size distribution (PSD) in abandoned farmland and different plantations in karst areas, and their impact on water repellency to provide references for its ecological restoration. First, for the shaddock plantation, citrus plantation, ginkgo plantation, Robinia pseudoacacia plantation, and abandoned farmland, the research objects, soil particle size and water drop penetration time were measured, and the fractal parameters of soil PSD were computed. Soil PSD characteristics' influence on water repellency was inferred according to, for example, correlation, redundancy, and stepwise regression analyses. Sand content in the shaddock plantation and clay content in the citrus plantation was the highest. The soil particles of abandoned farmland and plantations were primarily sand. The values of volume dimension D(0) in descending order were citrus plantation, shaddock plantation, ginkgo plantation, R. pseudoacacia plantation, and abandoned farmland. The values of information dimension D(1), correlation dimension D(2), and information dimension/volume dimension D(1)/D(0) in descending order were R. pseudoacacia plantation, ginkgo plantation, citrus plantation, abandoned farmland, and shaddock plantation. No significant differences were found in the symmetry degree Df, the spectral width Da of the singular spectral function, and the single fractal dimension D among the abandoned farmland and different plantations. Slight water repellency was observed in the abandoned farmland and different plantations. The degree of water repellency in descending order was R. pseudoacacia plantation > ginkgo plantation > abandoned farmland > citrus plantation > shaddock plantation. Significant correlations were found between fractal parameters and water repellency, and fractal parameters were suitable potential indicators for soil water repellency.